PERANAN MOTIVASI GUNA MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA PT. CENTRAL DISTRIBUSI UTAMA - K Kurniawansyah; Eka Hidayatunnisa (Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine the role of motivation in increasing employee productivity. This type of research is a qualitative research with a case study approach. The number of informants in this study were 8 informants consisting of managers, supervisors, admins, salespeople, helpers, and drivers. The method used for data collection is by using observation, interviews and documentation. The data were analyzed using the theory of Miles and Huberman which consisted of data collection, data reduction, data presentation, and conclusions. The results showed that the role of motivation to increase productivity carried out by the manager of PT. Central Distribution Main is not related to employee productivity, this can be seen from the way managers motivate employees but employee productivity remains stable because employee productivity is more towards meeting targets that must be met by employees but sales have decreased from the previous year due to the main factor, namely covid 19.